2016
DOI: 10.1016/j.jadohealth.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Mobile E-Health Intervention on Binge Drinking in Young People: The Digital–Alcohol Risk Alertness Notifying Network for Adolescents and Young Adults Project

Abstract: Our study provides evidence of population-level benefit at 2 weeks, attained with D-ARIANNA. This can be disseminated easily and economically among young people. However, additional components, including regular feedback and repeated administration by gamification, may be required to make this app suitable for longer term impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
1
39
0
1
Order By: Relevance
“…There was a noted reduction in binge drinking following the use of the app (Carrà et al, 2016), and the findings of this study provide further support for the acceptability of mobile technology, as a response rate of 82% was achieved, with 98% of participants reporting that the eHealth app was easy to use (Carrà et al, 2015). A wealth of evidence demonstrates that electronic communication based interventions are widely accepted by both young people (Britto et al, 2012;Dennison et al, 2013;Lim et al, 2012) and a number of other population groups (Arora et al, 2012;Patrick et al, 2009;Proudfoot et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
“…There was a noted reduction in binge drinking following the use of the app (Carrà et al, 2016), and the findings of this study provide further support for the acceptability of mobile technology, as a response rate of 82% was achieved, with 98% of participants reporting that the eHealth app was easy to use (Carrà et al, 2015). A wealth of evidence demonstrates that electronic communication based interventions are widely accepted by both young people (Britto et al, 2012;Dennison et al, 2013;Lim et al, 2012) and a number of other population groups (Arora et al, 2012;Patrick et al, 2009;Proudfoot et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, online information and other social media could be developed for youth on health‐related topics; recent research indicates one‐third of this age group uses online data to improve behavior (Wartella, Rideout, Zupancic, Beaudoin‐Ryan, & Lauricella, ). Illustrating this concept, one study reported that mobile E‐Health interventions for youth binge drinking showed short‐term efficacy in minimizing the behavior and could be further tested in a longer term fashion (Carrà et al., ). Other interventions could target stressors, many of which are modifiable, as they also negatively impact physical and mental health (McEwen, Gray, & Nasca, ).…”
Section: Processes and Changes Involved In Pubertymentioning
confidence: 99%
“…Several e-health solutions [i.e., A-CHESS ( 18 )] improve self-management by providing self-assessment modules and reminders and also allow for rapid contact with a support service to ensure swift responses in case of need. Other types of software [ORION ( 19 , 20 ), D-ARIANNA ( 21 , 22 ), Steering Clear program ( 23 )] optimize behavioral risk quantification (overdose for Orion, binge-drinking for D-ARIANNA, drink-driving for Steering Clear) via scalar self-assessment modules. These programs deliver rapid intervention in the form of guidelines, tips, motivational techniques and people to contact.…”
Section: Overview Of Technological Innovation Strategies In Substancementioning
confidence: 99%